2008
DOI: 10.1136/jnnp.2007.137554
|View full text |Cite
|
Sign up to set email alerts
|

Baseline differences between vascular cognitive impairment no dementia reverters and non-reverters

Abstract: These results suggest that Vascular CIND reversion may be a function of a combination of baseline neuropsychological function and location of cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Seven studies investigated progression of patients with VCI-ND and reported changes in cognitive function or incident dementia rates [12,15,23,29,31,37,40], though the length of follow-up varied as well as whether cognitive test scores or dementia rates were examined over time, thus making comparison difficult (table 2). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies investigated progression of patients with VCI-ND and reported changes in cognitive function or incident dementia rates [12,15,23,29,31,37,40], though the length of follow-up varied as well as whether cognitive test scores or dementia rates were examined over time, thus making comparison difficult (table 2). …”
Section: Resultsmentioning
confidence: 99%
“…Also used were the Clinical Dementia Rating (CDR) of 1+ [17], medical history [26,27], clinical diagnosis [29,30] and Mini Mental State Examination (MMSE) score ≤21 [33], or, in the case of one study, below the second percentile on the Korean MMSE [21]. Six studies excluded individuals using criteria for VaD [19,23,24,33,37,38]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a population study from Olmsted County, Minnesota, Kokmen et al [17] found that patients with a recent history of stroke had a ninefold [20]. In another study, frontal white matter hyperintensities on MRI were also associated with persistent cognitive changes after stroke [21].…”
Section: Vascular Risk Factors Transient Neurologic Attacks and Strmentioning
confidence: 97%